2016
DOI: 10.1177/1468796816654174
|View full text |Cite
|
Sign up to set email alerts
|

Digital belongings: The intersections of social cohesion, connectivity and digital media

Abstract: The rapid proliferation and ongoing transformation of digital technologies and social media platforms have had a substantial influence on the participatory cultures of young people and their associated social connections. This social/digital nexus raises important questions of social cohesion, with digital technologies at once augmenting social interaction whilst simultaneously creating an uneven landscape of access for participation. To address this interface of the digital and the social, this paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 32 publications
0
48
0
5
Order By: Relevance
“…Social media produces various ways to communicate with anyone through messages, images, audio and video based content [22]. This shift to social media communication is associated with increased availability of digital and cellular interfaces that influence the way people interact with each other through social media and other communication platforms [23]. It also affects education.…”
Section: Discussionmentioning
confidence: 99%
“…Social media produces various ways to communicate with anyone through messages, images, audio and video based content [22]. This shift to social media communication is associated with increased availability of digital and cellular interfaces that influence the way people interact with each other through social media and other communication platforms [23]. It also affects education.…”
Section: Discussionmentioning
confidence: 99%
“…For many, these platforms effectively fulfil an affective need. Multiple studies confirm the significance of virtual spaces within the daily lives and activities of modern populations and refugees are no exception (Dekker and Engbersen 2014;Marlowe et al 2016;Wilding 2012). Andrade and Doolin (2016) found that computers assisted refugees to evaluate resettlement opportunities and served as a portal that kept them connected to cultural roots and traditions.…”
Section: Integration Transnational Network and Social Mediamentioning
confidence: 94%
“…Including the following. The first digital technology and social media platforms have had a major influence on the participatory culture of young people in the context of social cohesion [13]. Secondly, the community has succeeded in utilizing social media as a counterweight, reminder, and summarization of new social movements in the environmental, educational and social fields [14].…”
Section: A New Media New Civicsmentioning
confidence: 99%